Proteasomal degradation induced by DPP9‐mediated processing competes with mitochondrial protein import. (20th August 2020) - Finger, Yannik; Habich, Markus; Gerlich, Sarah; Urbanczyk, Sophia; van de Logt, Erik; Koch, Julian; Schu, Laura; Lapacz, Kim Jasmin; Ali, Muna; Petrungaro, Carmelina; Salscheider, Silja Lucia; Pichlo, Christian; et al.
Abstract: Plasticity of the proteome is critical to adapt to varying conditions. Control of mitochondrial protein import contributes to this plasticity. Here, we identified a pathway that regulates mitochondrial protein import by regulated N‐terminal processing. We demonstrate that dipeptidyl peptidases 8/9 (DPP8/9) mediate the N‐terminal processing of adenylate kinase 2 (AK2) en route to mitochondria. We show that AK2 is a substrate of the mitochondrial disulfide relay, thus lacking an N‐terminal mitochondrial targeting sequence and undergoing comparatively slow import. DPP9‐mediated processing of AK2 induces its rapid proteasomal degradation and prevents cytosolic accumulation of enzymatically active AK2. Besides AK2, we identify more than 100 mitochondrial proteins with putative DPP8/9 recognition sites and demonstrate that DPP8/9 influence the cellular levels of a number of these proteins. Collectively, we provide in this study a conceptual framework on how regulated cytosolic processing controls levels of mitochondrial proteins as well as their dual localization to mitochondria and other compartments. Synopsis: Control of mitochondrial protein import contributes to adaptation of mitochondrial function. DPP9‐dependent N‐terminal processing of cytosolic precursor proteins controls their mitochondrial levels and clearance of cytosolic unwanted precursors via proteasomal degradation in human cells. Dipeptidyl peptidases 8/9 (DPP8/9) mediate the N‐terminal processing of adenylate kinase 2 (AK2). N‐terminal processing of AK2 precursor induces its proteasomal degradation. Proteasomal degradation prevents cytosolic accumulation of enzymatically active AK2 and limits mitochondrial AK2 levels. More than 100 mitochondrial proteins contain putative DPP8/9 recognition sites. Abstract : DPP9‐dependent N‐terminal processing of cytosolic precursor proteins controls their mitochondrial levels and clearance of unwanted precursors via proteasomal degradation in human cells.